PEMANFAATAN CORN GLUTEN MEAL SEBAGAI SUMBER PROTEIN PEMBENTUK STRUKTUR ROTI BERBASIS TEPUNG SINGKONG - Larisa, Ratna
White bread is a wheat flour-based food product with a high gluten content. Gluten functions as a trap for CO2 gas produced during the yeast fermentation process. However, gluten cannot be digested by people with celiac disease because they have an intolerance to gluten and by children with special needs. Therefore, gluten-free flour-based bread began to be developed. One local commodity that can be used as an alternative to wheat flour is fermented cassava flour. However, the absence of gluten in this flour will produce a bread texture that is not hollow, soft, or moist. One ingredient that can increase the viscoelastic properties of bread is corn prolamin or zein. One ingredient that contains large amounts of zein is Corn Gluten Meal or CGM. The CGM currently on the market is still within animal feed standards so it is necessary to extract zein first before using it in the bread making process. The extraction and isolation process of zein from CGM will use 70% ethanol solvent. The aim of this research was to determine the effect of adding zein and CGM on the sensory aspects of bread by analyzing the specific volume, appearance of bread crumbs and texture. The research was carried out by varying the types of additives added, namely; Zein isolates from lab-scale CGM, hydrocolloids, and flour variations. Apart from that, the addition of zein and CGM was also varied by; 1, 2, 3 and 4 g per 20 grams of fermented cassava flour mixture and additives. Based on research that has been carried out, the variation of bread that has the best texture quality is the variation of bread based on fermented cassava flour with the addition of 2% HPMC and 10% zein isolate. The addition of zein isolate can increase the viscoelasticity of the dough, but will produce bread with a very hard crumb.